Micronutrient, Antioxidant, and Oxidative Stress Status in Children With Severe Cerebral Palsy. Issue 1 (18th May 2012) - Schoendorfer, Niikee C.; Vitetta, Luis; Sharp, Nita; DiGeronimo, Michelle; Wilson, Gary; Coombes, Jeff S.; Boyd, Roslyn; Davies, Peter S. W.
Abstract : Background : Markers indicative of micronutrient and antioxidant status in children with cerebral palsy (CP) were explored due to these children's well‐documented issues with food intake and the limited biochemical literature. Materials and Methods : Children aged 4 to 12 years with marked CP (n = 24) and controls (n = 24) were recruited. The CP group represented orally (O) or enterally fed (E) children. Concentrations of red cell folate (RCF), magnesium, superoxide dismutase (SOD), glutathione reductase, and peroxidase were measured, as well as serum methylmalonic acid and vitamin C. Plasma hemoglobin, C‐reactive protein, α‐tocopherol, cholesterol, zinc, protein carbonyls, and total antioxidant capacity were also quantified. Results : Data are reported as mean (SD) and z scores where values differ with age. Many similarities existed, but zinc z scores were reduced in O (–1.10 [0.83]) vs controls (–0.54 [0.54]) ( P < .05), as well as for glutathione reductase in O (10.15 [1.69]) vs E (12.22 [2.41]) and controls (11.51 [1.67]) ( P < .05). RCF was greatly increased in E (1422 [70]) vs O (843 [80]) and controls (820 [43]) ( P < .001). SOD was decreased in E (24.3 [1.4]) vs controls (27.0 [2.8]) ( P < .05). Conclusion : Considering their vast impact on physiology, micronutrients should be routinely monitored in orally fed children with swallowing disorders and dietary limitations. Excessive intakes, particularly long term in enterally fed children, should also be monitored in view of their potential for competitive inhibition, particularly at high levels.